The Effect of Work Motivation and Training on Job Satisfaction at Politeknik Muhammadiyah Makassar - Ilham, Naura Aulia; Haer, M. Ilham Wardhana; Burhanuddin, Burhanuddin (PT Smart Media Makassar, 2025)
This study aims to analyze the influence of work motivation and training on job satisfaction at the Muhammadiyah Makassar Polytechnic. In a competitive era like today, effective work motivation and training can play an important role in improving employee performance and job satisfaction. This study uses a quantitative approach with a survey method, involving 60 respondents from lecturers at the Muhammadiyah Makassar Polytechnic. Data were collected through questionnaires distributed to lecturers at the Muhammadiyah Makassar Polytechnic and analyzed using multiple linear regression. The results of the study showed that work motivation had a significant effect on job satisfaction, the higher the work motivation, the higher the level of job satisfaction experienced by polytechnic lecturers. as well as training provided by the institution. Overall, both work motivation and training have been proven to increase job satisfaction of lecturers at the Muhammadiyah Makassar Polytechnic. This study provides implications for institutional management to pay more attention to these factors in an effort to improve the performance and welfare of lecturers.